An application of the AHP in evaluating the sales channels of the Chinese flower market. (1st January 2013) - Lee, Tzong-Ru; Yang, Shu-Hui; Khamkaew, Thanchanok
In this case study, the analytic hierarchy process (AHP) is applied to evaluate the marketing modes of the Shanghai flower market, because of the large flower consumption volume and the location of gathering flower products from nationwide before export. The relative weights of four elements of marketing tools (4Ps), and eventually the optimal marketing mode is selected. The results provide two different modes of marketing strategies, such as packaging design, on-line advertisement, and authorized agencies, to gain the competitiveness. The results obtained provide useful implications for developing innovation and learning for flower industries in developing economies.